The Influence of Social Media Communication, Product Quality, and Promotion on Purchase Intention - Ida Ayu Nyoman Ari Cendani Wati; Ni Luh Putu Indiani (Almana : Jurnal Manajemen dan Bisnis, 2022)
Abstract: In the last 10 years, Indonesia's beauty and personal care industry grew around 12%, with a market value of 33 trillion Rupiah in 2016. The business in Indonesia is predicted to experience the largest growth compared to other countries in Southeast Asia. This raises interest in analyzing the factors influencing consumer purchase intention in body care products. The purpose of this study was to analyze the influence of social media communication, product quality, and promotion on purchase intention. The data collection method is a survey method with questionnaires. The sample size was 105 respondents. Multiple linear regression analysis techniques were used to test the influence of the independent variable on the dependent variable. The study's results found that social media communication, product quality, and promotion positively and significantly influence purchase intention. The brand needs to build good relationships with consumers through social media to encourage purchase intention. In terms of quality, the brand should be able to create a unique and distinctive quality that consumers can accept. In the promotion aspect, the brand should show a responsible attitude when complaints occur, such as providing a money-back guarantee.